Using Critical Thinking Technology in Russian Language and Reading Literacy Lessons (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The characteristics of the concept of “critical thinking” are presented based on the analysis of scientific and scientific-methodological literature, and the author’s generalized definition of this concept is given. The importance and features of the formation of critical thinking skills among primary school students in Russian language and reading literacy lessons are revealed. In the process of developing critical thinking, it is necessary to identify criteria for determining the level of development of this type of skills and indicators for assessing students’ activities in this direction. In this regard, criteria for determining and indicators for assessing the development of critical thinking skills are presented.